2001
DOI: 10.1002/1615-4169(200108)343:6/7<607::aid-adsc607>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of Reversible Denaturation and Elevated Melting Temperature in a Microbial Haloalkane Dehalogenase

Abstract: Haloalkane dehalogenases have the potential for use in high‐value biocatalytic processes to convert haloalkanes into epoxides via intermediate haloalcohols. Initial bioreactor studies probing the hydrolysis of 1,2,3‐trichloropropane by immobilized wild‐type dehalogenase isolated from Rhodococcus rhodochrous demonstrated, however, that productivity was too low to realize a commercially viable process. A strategy to increase enzyme performance was undertaken to increase the reaction temperature, however it was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 0 publications
2
46
0
Order By: Relevance
“…Completely arational methods that subject the entire gene to saturation mutagenesis at every site in the corresponding protein offer one way to explore the space of all single amino acid mutations, but they often require extensive molecular biology efforts to manufacture and manage the screening of hundreds of small libraries [30][31][32][33][34] or thousands of sequence-verified clones [35]. New developments for randomly accessing a wider array of mutations include random insertion and deletion mutagenesis (RID) [36] and trinucleotide exchange (TriNEx) protocols [37].…”
Section: B Arational Methodsmentioning
confidence: 99%
“…Completely arational methods that subject the entire gene to saturation mutagenesis at every site in the corresponding protein offer one way to explore the space of all single amino acid mutations, but they often require extensive molecular biology efforts to manufacture and manage the screening of hundreds of small libraries [30][31][32][33][34] or thousands of sequence-verified clones [35]. New developments for randomly accessing a wider array of mutations include random insertion and deletion mutagenesis (RID) [36] and trinucleotide exchange (TriNEx) protocols [37].…”
Section: B Arational Methodsmentioning
confidence: 99%
“…Secondary characterization showed that residues Ala190 and Phe191 were mutational hotspots. The same technique was used to increase the thermal stability of a microbial haloalkane dehalogenase [22]. Subsequent recombination of the single site mutations improved the half-life at 55°C from 11 min for the parental enzyme to 29,000 min and the melting temperature of the final variant was increased 8°C.…”
Section: Non-recombinative Methodsmentioning
confidence: 99%
“…By using error prone PCR and DNA shuffling, Bosma et al (2002) generated a DhaA mutant (e.g., a variant called DhaAM2 with the mutations C176Y and Y273F) that had three times higher catalytic efficiency ( k cat / K m   =  280 s −1  M −1 ) than wild-type enzyme. Similarly, Gray et al (2001) performed in vitro evolution studies which also yielded a mutant with a substitution at position 176 and a mutation close to the N terminus that showed higher activity with TCP as compared to wild-type, and further mutations enhanced the stability of the enzymes.…”
Section: Biotransformation and Biodegradationmentioning
confidence: 99%